The acute effects of exercise on the microvascular volume of Achilles tendons in healthy young subjects. (13th February 2013) - Pingel, Jessica; Harrison, Adrian; Suetta, Charlotte; Simonsen, Lene; Langberg, Henning; Bülow, Jens
Summary Background Real‐time harmonic contrast‐enhanced ultrasound (CEU) is used in several diseases to visualize the microvascularization in various tissues, due to its high sensitivity. Aim The aim of the present study was to investigate whether CEU could be used to detect an increase in the microvascular volume (MV) in healthy tendon tissue in response to exercise comprising a 1‐h run. Methods After a bolus injection of the ultrasound contrast SonoVue®, CEU measurements of (MV) in the Achilles tendon were taken prior to exercise, immediately after a 1‐h run, and 24 h after exercise in nine healthy young subjects (seven men and two women) mean age 31 ± 4 years. In addition, the effect of 15 min of arm cycling exercise on the flow within the Achilles tendon was tested in four athletes (mean age 33 ± 6 years) using the CEU method before and after exercise. Results The present data show a significant increase in the (MV) of the Achilles tendon for all subjects following the run compared with before exercise. No significant change in (MV) was seen in the Achilles tendon after 15‐min arm cycling exercise (P = 0·96). This indicates that the increase in microvascular blood volume within the Achilles tendon in response to running is a local response. Conclusion The present data reveal that real‐time harmonic CEU can be used to determine the MV of healthy Achilles tendons both at rest and after 1 h of running exercise.